Photo‐Promoted Nitrogen‐Centered Radical Mediated Intermolecular Aminative Carbonylation of Tertiary Allyl Alcohols to Access β‐Amino Ketones through (Hetero)Aryl Migration - Ming Hou; Yuanrui Wang; Hefei Yang; Jiajun Zhang; Prof. Dr. Xiao‐Feng Wu (ChemistryEurope)
Abstract Carbon monoxide, as a crucial C1 synthon, has been widely used in the difunctionalization of alkenes. Additionally, nitrogen‐centered radicals (NCRs) are also effective intermediates for constructing C−N bonds. Herein, a nitrogen‐centered radical‐mediated aminative carbonylation strategy for producing β‐amino ketones from tertiary allyl alcohols has been disclosed. Good yields of β‐amino ketones with different functional groups were generated effectively under light irradiation.